Virus : An Illustrated Guide to 101 Incredible Microbes - Roossinck, Marilyn J. (Princeton University Press, 2016)
This stunningly illustrated book provides a rare window into the amazing, varied, and often beautiful world of viruses. Contrary to popular belief, not all viruses are bad for you. In fact, several are beneficial to their hosts, and many are crucial to the health of our planet. Virus offers an unprecedented look at 101 incredible microbes that infect all branches of life on Earth-from humans and other animals to insects, plants, fungi, and bacteria.Featuring hundreds of breathtaking color images throughout, this guide begins with a lively and informative introduction to virology. Here readers can learn about the history of this unique science, how viruses are named, how their genes work, how they copy and package themselves, how they interact with their hosts, how immune systems counteract viruses, and how viruses travel from host to host. The concise entries that follow highlight important or interesting facts about each virus. Learn about the geographic origins of dengue and why old tires and unused pots help the virus to spread. Read about Ebola, Zika, West Nile, Frog virus 3, the Tulip breaking virus, and many others-how they were discovered, what their hosts are, how they are transmitted, whether or not there is a vaccine, and much more. Each entry is easy to read and includes a graphic of the virus, and nearly every entry features a colorized image of the virus as seen through the microscope.Written by a leading authority, this handsomely illustrated guide reveals the unseen wonders of the microbial world. It will give you an entirely new appreciation for viruses.